Les homophones grammaticaux, portrait actuel des occurrences et des taux de réussite chez des élèves de 9 à 12 ans - Giguère, Marie-Hélène; Aldama, Rebeca (Canadian Journal of Applied Linguistics, 2020)
This study aims to describe occurrences of homophone words and frequencies of grammatical homophone errors in 119 free texts of 9 to 12-year-old Quebec students from a list of 22 series of homophones. This analysis made it possible to confirm that grammatical homophones are widely used by students, but that, considering all the possibilities in the different series, they are more successful than we had anticipated. Thus, our results made it possible not only to establish a current portrait of the homophone words spontaneously used by 9 to 12-year-old students in their texts, but also to identify constants in the successes (related to the frequency). Some syntactic contexts were also analyzed to identify priority areas to work on for teachers. Finally, our study identifies areas of vulnerability among students based on three factors: gender, age, and socio-economic background. The discussion concludes with recommendations for teaching grammatical categories.